Adherence to the Mediterranean diet is associated with lower abdominal adiposity in European men and women. - Romaguera, D; Norat, T; Mouw, T; May, A; Bamia, C; Slimani, N; Travier, N; Besson, H; Luan, J; Wareham, N; Rinaldi, S; Couto, E; et al. (2009)
Given the lack of consistent evidence of the relationship between Mediterranean dietary patterns and body fat, we assessed the cross-sectional association between adherence to a modified Mediterranean diet, BMI, and waist circumference (WC). A total of 497,308 individuals (70.7% women) aged 25-70 y from 10 European countries participated in this study. Diet was assessed at baseline using detailed validated country-specific questionnaires, and anthropometrical measurements were collected using standardized procedures. The association between the degree of adherence to the modified-Mediterranean Diet Score (mMDS) (including high consumption of vegetables, legumes, fruits and nuts, cereals, fish and seafood, and unsaturated:saturated fatty acids ratio; moderate alcohol intake; and low consumption of meat and meat products and dairy products) and BMI (kg.m(-2)) or WC (cm) was modeled through mixed-effects linear regression, controlling for potential confounders. Overall, the mMDS was not significantly associated with BMI. Higher adherence to the Mediterranean diet was significantly associated with lower WC, for a given BMI, in both men (-0.09; 95% CI -0.14 to -0.04) and women (-0.06; 95% CI -0.10 to -0.01). The association was stronger in men (-0.20; 95% CI -0.23 to -0.17) and women (-0.17; 95% CI -0.21 to -0.13) from Northern European countries. Despite the observed heterogeneity among regions, results of this study suggest that adherence to a modified Mediterranean diet, high in foods of vegetable origin and unsaturated fatty acids, is associated with lower abdominal adiposity measured by WC in European men and women.